Isoleucine in segregated early weaning and transition diets - Linneen, S.K.; Tokach, Michael D.; DeRouchey, Joel M.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
Two studies were conducted to test the effect of isoleucine amount and source on nursery pig performance. In Exp. 1, a total of 194 pigs were used in a 10-d study in a research facility to test the effects of isoleucine rate in high or low lysine diets. Dietary treatments included either high or low lysine and high or low isoleucine in a 2 × 2 factorial arrangement. High-lysine diets were formulated to 1.56% TID lysine, and low-lysine diets were formulated to 1.30% TID lysine. Highisoleucine diets contained approximately 60% TID isoleucine:lysine, whereas low-isoleucine diets contained approximately 49% isoleucine: lysine. Overall (d 0 to 10), there were no significant lysine by isoleucine interactions (P<0.23). From d 0 to 5, pigs fed diets containing high lysine had higher (P<0.02) ADG and tended to have higher (P<0.09) ADFI, compared with performance of pigs fed diets containing low lysine. Also, pigs fed diets containing high isoleucine had a weak tendency for higher (P<0.17) ADG and ADFI, compared with performance of pigs fed diets containing low isoleucine, because pigs fed high isoleucine and low lysine gained and ate more than pigs fed low isoleucine and low lysine. Overall (d 0 to 10), pigs fed diets containing high lysine had higher (P<0.01) ADG and improved (P<0.01) F/G, compared with performance of pigs fed diets containing low lysine. There was a weak tendency to have improved (P<0.18) ADFI for pigs fed diets containing either high lysine or high isoluecine. In Exp. 2, a total of 1,540 pigs were used in a 21-d growth assay in a commercial facility to test the effects of increased dietary L-isoleucine from different isoleucine sources on nursery pig performance. Treatments included: control (standard SEW and transition diets) or the control with increased isoleucine from added L-isoleucine, soybean meal, wheat gluten, or poultry meal. During the SEW period (d 0 to 5), pigs fed diets containing added L isoleucine had better (P<0.05) ADG than did pigs fed the control or diets containing added soybean meal. Also, pigs fed the diet containing wheat gluten had better (P<0.05) ADG than did pigs fed added soybean meal. Pigs fed diets containing added L-isoleucine had better (P<0.05) F/G than did pigs fed the control or diets containing added soybean meal. Also, pigs fed diets containing wheat gluten had better (P<0.05) F/G than did pigs fed added soybean meal. During the transition period (d 5 to 10), pigs fed diets containing poultry meal had lower (P<0.05) ADG than did pigs fed the control diet or added soybean meal. Also, pigs fed diets containing added soybean meal had better (P<0.05) F/G than did pigs fed diets with added L-isoleucine or poultry meal. From d 0 to 10, there were no differences in ADG or ADFI between treatments; nonetheless, F/G was better (P<0.05) for pigs fed added soybean meal than for pigs fed the control diet. Overall (d 0 to 21), there were no differences in ADG or ADFI between treatments, but F/G was better (P<0.05) for pigs fed diets with added soybean meal or wheat gluten than for pigs fed diets containing added L-isoleucine. For the economic analysis, pigs fed the diets containing wheat gluten had higher (P<0.05) cost per pound of gain from d 0 to 5, d 5 to 10, and d 0 to 10 than did pigs fed all other diets. From d 0 to 5, margin over feed was higher (P<0.05) for the diets with added L-isoleucine or poultry meal, compared with the diet containing wheat gluten. From d 5 to 10, margin over feed was higher (P<0.05) for diets containing added soybean meal than for diets containing wheat gluten, added Lisoleucine, or poultry meal. From d 0 to 10, margin over feed was lowest (P<0.05) for the diet containing wheat gluten, compared with all other diets. These studies indicate that maintaining an adequate amount of isoleucine is critical in diets immediately after weaning, and the addition of L-isoleucine is an economical means of increasing isoleucine in the SEW diet to improve performance.
Keywords: Isoleucine; Amino acid; Nursery pig; Swine